Origins and development of mirroring mechanisms: A neuroconstructivist framework. (10th August 2015) - Quadrelli, Ermanno; Turati, Chiara
Abstract : The current review examines models developed to answer questions about the origins and early developmental processes determining the emergence of mirroring mechanisms and considers the debate about the role of the motor system in action understanding. Strengths and points of criticism deriving from existing alternative positions are illustrated. Particular emphasis is put on the neuroconstructivist framework with the aim of evaluating whether the hypotheses driven by this approach are in line with the available evidence. Within the neuroconstructivist framework, a novel model is proposed in which the direct‐matching and action reconstruction viewpoints on action understanding processes can be integrated by assuming a developmental perspective. It is suggested that mirroring mechanisms are shaped by a domain‐relevant narrowing process driven by sensorimotor experience and that action understanding can take advantage of both top‐down and bottom‐up processes, in a multilevel and dynamic fashion.